2023
DOI: 10.3390/jcdd10020090
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical versus Bioprosthetic Aortic Valve Replacement in Middle-Aged Adults: A Systematic Review and Meta-Analysis

Abstract: Background: Mechanical prostheses and bioprosthetic prostheses have their own advantages and disadvantages. Mechanical ones are recommended for younger patients (<50 years old), and bioprosthetic ones are recommended for older patients (>70 years old). There is still debate regarding which kind of prosthesis is better for middle-aged patients (50 to 70 years old) receiving aortic valve replacement (AVR). To solve this problem, we conducted this meta-analysis. Given that only one randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Among numerous studies comparing the clinical outcomes of mechanical and bioprosthetic AVR in middle- aged patients, some studies found that long-term survival was significantly greater with mechanical AVR than bioprosthetic AVR [ 3 , 8 , 10 - 17 ], whereas others found no significant survival difference [ 18 - 21 ]. The most recent meta-analysis, which included 22 publications and involved 32,298 patients, reported greater long-term survival with mechanical AVR than bioprosthetic AVR among individuals aged 50 to 70 years [ 13 ]. However, they also reported that when they reduced the upper limit of the age range to 65 years, the survival benefit of the mechanical valve disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among numerous studies comparing the clinical outcomes of mechanical and bioprosthetic AVR in middle- aged patients, some studies found that long-term survival was significantly greater with mechanical AVR than bioprosthetic AVR [ 3 , 8 , 10 - 17 ], whereas others found no significant survival difference [ 18 - 21 ]. The most recent meta-analysis, which included 22 publications and involved 32,298 patients, reported greater long-term survival with mechanical AVR than bioprosthetic AVR among individuals aged 50 to 70 years [ 13 ]. However, they also reported that when they reduced the upper limit of the age range to 65 years, the survival benefit of the mechanical valve disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…3A ). Among the comparative studies analyzing valve types in middle-aged AVR, only a few reported a significant difference in the occurrence of stroke [ 12 , 13 , 15 , 18 , 20 , 24 , 28 - 30 ]. Stroke is a devastating complication that may occur early or late after prosthetic valve replacement and results from embolism, intracranial hemorrhage, or both [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical repair of the aortic valve is a significant heart procedure that ranks second in cardiac surgery and among the top heart treatments. Depending on the patient's features, a biological, mechanical, or autopericardium replacement may be chosen [16]. Depending on the surgeon's discretion, there are various implantation procedures for aortic valve repair, including U-shaped sutures on spacers, an interrupted sew technique for thin aortic valve rings, and continuous sutures [17].…”
Section: Discussionmentioning
confidence: 99%